Factores socioeconómicos relacionados a los delitos de corrupción de funcionarios y servidores públicos, peculado y colusión, en la Municipalidad Provincial de Maynas, 2019 a 2021 - Samamé Ortiz, Brian Karol (2025)
The objective of this work is to determine the relationship between socioeconomic factors and corruption offenses committed by public officials, specifically embezzlement and collusion, in the Provincial Municipality of Maynas between 2019 and 2021. The study, with a mixed-method approach and cross-sectional design, worked with a sample of 10 judicial records, 25 prosecutorial case files, and 56 records from the Specialized Prosecutor’s Office for Corruption of Officials in Loreto. Data collection was carried out using a socioeconomic factors form related to public corruption, validated by three experts. In the results, in 2019, 50 men and 2 women were prosecuted; in 2020, 22 men and 2 women; and in 2021, 11 men. Regarding educational level, most had higher education, although there were also cases with secondary education. In terms of remuneration, the majority earned more than one thousand soles, while fewer registered lower amounts or did not specify. Concerning positions, the defendants mainly held responsibility roles such as mayors, managers, deputy managers, and department heads. The findings show a significant relationship between age, level of education, remuneration, and position held with the commission of corruption crimes. This suggests that socioeconomic factors influence the occurrence of embezzlement and collusion, providing valuable insights for the understanding of criminal law in cases of public corruption.